1994
DOI: 10.1021/bi00206a025
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the Water-Oxidizing Complex in Manganese-Depleted Photosystem II Complexes by Using Synthetic Binuclear Manganese Complexes.

Abstract: The efficiency of synthetic binuclear manganese complexes in reconstituting PS II electron flow and oxygen-evolution capacity was analyzed in PS II enriched preparations deprived of their manganese and of the extrinsic regulatory subunits. Measurements of the variable fluorescence induced by actinic illumination with continuous light led to the following results: (a) the synthetic binuclear complexes are more efficient than MnCl2 in establishing a PS II electron flow; (b) an almost complete restoration is achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…3 shows the double reciprocal plots of this dependence at pH 5. (20,21). In A, 0.4 M MnCl2 (2 Mn͞RC) was added.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 shows the double reciprocal plots of this dependence at pH 5. (20,21). In A, 0.4 M MnCl2 (2 Mn͞RC) was added.…”
Section: Resultsmentioning
confidence: 99%
“…The BBY [subchloroplast preparation isolated by the method worked out by Berthold, Babcock, and Yocum (18)] PSII membrane fragments were prepared as described (18,19). A complete (Ͼ95%) removal of Mn from the membrane fragments was carried out using 1 M Tris⅐HCl (pH 8.0) plus 0.5 M MgCl 2 (17) or N,N,NЈ,NЈ-tetramethylethylenediamine (TEMED) (20,21) treatments. The preparations were stored in liquid nitrogen or at Ϫ80ЊC at a Chl concentration of 10 mg͞ml after the addition of 10% glycerol or 0.4 M sucrose to the medium.…”
Section: Methodsmentioning
confidence: 99%
“…It seems, therefore, that Cu(II) inhibitory and TEMED treatment effects are the consequence of different molecular mechanisms. Since TEMED treatment removes the extrinsic proteins and the manganese cluster of the PSII donor side (35), it can be suggested that the Cu(II)-inhibitory site, in these experimental conditions, is not located on the donor side of PSII. In addition, the presence of Cu(II) did not modify the D1 protein degradation in the non-oxygenic (i.e.…”
Section: Effect Of Cu(ii) On Oxygen Evolution Activity and D1 Degradamentioning
confidence: 95%
“…This sample exhibited oxygen evolution rates of 560 mol of O 2 ⅐mg of Chl Ϫ1 ⅐h Ϫ1 in the presence of 0.5 mM 2,6-dichlorobenzoquinone as artificial electron acceptor. Non-oxygenic PSII membranes were prepared by incubation of the intact PSII membranes (0.2 mg of Chl⅐ml Ϫ1 ) in a suspension containing 20 mM TEMED, 0.5 M MgCl 2 , and 20 mM Mes-NaOH, pH 6.5 (35). After centrifugation at 20,000 ϫ g the pellet was washed twice in a buffer solution of 35 mM NaCl and 20 mM Tris-HCl, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation